(untitled) (Research, Society and Development, 2021)
Introduction: Subcutaneous emphysema is an accident where the forced introduction of air into the tissues occurs, which in dentistry can appear after the use of a high-speed pen or triple syringe. The swelling associated with emphysema can be mistaken for bruising, allergies or infections. The differential diagnosis is often related to the presence of crackles on palpation, associated or not, with pain. Treatment is prophylactic and palliative, since the problem tends to resolve spontaneously. Objective: To report a clinical case of subcutaneous emphysema and extraction of third molars, discussing the importance of differential diagnosis to guide the treatment of this complication. Case report: A 22-year-old female patient attended the oral and maxillofacial surgery service of a public hospital in Recife-PE, complaining of pain in the lower left third molar region. During the surgical procedure, it was necessary to use a high-speed pen to perform osteotomy and odontosection of tooth 38. At the end of the surgery, there was an increase in volume in the left periorbital region, compatible with subcutaneous emphysema. After 7 days postoperatively, spontaneous resolution of emphysema was observed. Discussion: According to the current literature, after the emphysema is already under a dermal layer, the air may remain at the surgery site or continue to spread along the facial spaces, depending on the permanence of the air jet. Conclusion: The correct diagnosis of subcutaneous emphysema was effective in ruling out other complications, guiding the management of the reported case, in addition to preventing the emphysema from evolving to an infection involving the cervicofacial or thoracic region.